Beyond the Numbers: Reimagining Human Performance Evaluation in the Age of Industry 5.0 - Awad Mabrouk (Solo International Collaboration and Publication of Social Sciences and Humanities, 2026)
Objective: This study aims to critically reimagine human performance evaluation in the emerging context of Industry 5.0, which emphasizes human-centricity, sustainability, and societal value over mere productivity metrics. Traditional evaluation systems—rooted in Industry 3.0 and 4.0—have prioritized efficiency, control, and standardized outputs. Theoretical framework: However, such frameworks often neglect employee well-being, creativity, and holistic growth. Drawing upon Human-Centered Design Theory and Socio-Technical Systems Theory, this research proposes a paradigm shift toward a more inclusive and developmental model of appraisal. Literature review: A comprehensive literature review reveals major limitations in conventional performance appraisal systems, including inherent bias, infrequent feedback, rigid ranking mechanisms, and a narrow focus on quantitative metrics. These shortcomings clash with the core values of Industry 5.0, where technology is meant to serve—not replace—human potential. The review further highlights emerging best practices that integrate empathy, personalization, and AI-enhanced feedback loops. Methods: This research adopts a qualitative methodology, including semi-structured interviews with HR professionals, organizational psychologists, and digital transformation leaders across diverse industries. Content analysis is applied to uncover themes and insights related to current challenges and future possibilities in performance evaluation. Results: Findings suggest that performance systems aligned with Industry 5.0 should prioritize continuous feedback, psychological safety, and individualized development pathways. Additionally, AI and data analytics are found to be powerful enablers for real-time insights, yet their implementation requires careful ethical consideration and transparency. The shift also demands a redefinition of HR competencies to balance technological fluency with emotional intelligence. Implications: The study's implications are significant for organizational design, talent management, and leadership development. By moving from a "control and correct" approach to an "empower and grow" model, organizations can cultivate more agile, innovative, and resilient workforces. Novelty: The novelty of this research lies in its integration of human-centered theory with digital capabilities to offer a practical and future-ready framework for performance evaluation.